Zeichnung als einsiedler Drawing '89. (Wien : Galerie REM, 1989)
Adrian X, Robert ; Bajic, Mrdan ; Battisti, Peter ; Blaas, Franz ; Bodnar, Eva ; Böröcz, Andras ; Brandner, Angela ; Eberl, Irma ; Gironcoli, Bruno ; Graf, Franz ; Gudac, Vladimir ; Held, Georg ; Hien, Albert ; Janos, Sugár ; Kaligofsky, Ad ; Lombardi, Ines ; Obholzer, Walter ; Priesch, Hannes ; Scheibl, Hubert ; Schu, Manfredu ; Skrlin, Nada ; Trawöger, Ernst ; Troger, Gustav ; Türtscher, Franz ; Vallazza, Hugo ; Walde, Martin
Zeichnung als einsiedler Drawing '89, Galerie REM, Wien, 1989
Duits
kunstcatalogus